Hydroprinting Technology to Transfer Ultrathin, Transparent, and Double‐Sided Conductive Nanomembranes for Multiscale 3D Conformal Electronics. Issue 1 (2nd December 2021) - Yoo, Dongwoo; Kim, Seonghyeon; Cho, Woosung; Park, Jaechan; Kim, Joonwon
Abstract: Transparent multiscale 3D conformal electronics using hydroprinting with polyvinyl alcohol (PVA) as a sacrificial layer to transfer networks of silver nanowires (AgNWs) without a carrier layer is developed. However, AgNWs are known to disperse on water surfaces during the transfer process. Therefore, a functional film is developed by simultaneously welding and embedding AgNWs in the PVA through a simple one‐step thermal pressing, demonstrating that ultrathin, transparent, and double‐sided conductive/patterned nanomembranes with welded AgNWs can float on water without dispersion. The nanomembrane with an excellent figure of merit of 1200, a low sheet resistance of 16.2 Ω sq −1, and a high transmittance of 98.17% achieves conformal contact with excellent step surface coverage of complex macro‐ and microstructures because of its nanoscale thickness (54.39 nm) and numerous deformable micro‐ and nanopores. Furthermore, the double‐sided conductive nanomembranes facilitate wiring and layer‐by‐layer assembly, regardless of the transfer direction of the surface. As a proof‐of‐concept demonstration, a nanomembrane‐based aneurysm sensor is developed. Its high transparency enables coil embolization, and the sensor can measure the pushing force of the coil within an aneurysm in an endovascular simulator. Moreover, this newly developed hydroprinting technology provides a new method for the fabrication of transparent multiscale 3D conformal electronics. Abstract : Novel hydroprinting technology to transfer ultrathin, transparent, and double‐sided conductive/patterned nanomembranes for multiscale 3D conformal electronics is demonstrated via the fabrication of a functional film. The nanomembrane enables conformal contact with excellent step surface coverage of complex macro‐ and microstructures. The double‐sided conductive nanomembrane enables wiring and layer‐by‐layer assembly regardless of the transfer direction of the surface.